Estudo das três dimensões do problema didático da derivada de uma função - Oliveira, Luis Carlos Barbosa de (2022)
The research problem of this thesis deals with the notion of derivative, of the Differential and Integral Calculus, considering it a mathematical object that has contributed to scientific and technological development, but which has presented difficulties in its learning. Thus, we decided to undertake this research in order to understand how the aspects linked to the epistemological, economic-institutional and ecological dimensions of the didactic problem related to the derivative can contribute to the development of a Reference´s Didactic Model as a basis for the proposition of Study and Research Rout for the teaching/learning of the derivative at the Higher level of education. To achieve this goal, we will be guided by the question "What contributions can epistemological, economic-institutional and ecological studies make to the development of a Reference´s Didactic Model supported by Study and Research Activities aimed at teaching secondary education in Higher Education ? , which helped us to design our general objective, which consists of conducting studies that allow us to understand aspects related to the epistemological, economic-institutional and ecological dimensions of the didactic problem associated with the derivative, capable of contributing to the development of a Didactic Reference Model- MDR, as a basis for proposing Teaching and Research Activities aimed at teaching derivatives in Higher Education. To guide us in the analysis of the studies obtained, we will use the Anthropological Theory of Didactics as a theoretical framework